IMPACT OF ADAPTATION TO CLIMATE CHANGE ON NET RETURNS IN SMALLHOLDER PIGEON PEA PRODUCTION SYSTEMS IN SEMI-ARID KENYA - Matere, Stella Jane; Busienei, Rono John; Mbatia, Oliver Lee Ernest (International Journal of Agriculture, 2020)
Purpose: Improved pigeon pea varieties were promoted in semi-arid areas of Kenya to improve smallholder pigeon pea production systems resilience to climate change. However, the impact of adoption is unknown. This study was carried out to evaluate the impact of adoption on farming households' net farm returns in semi-arid South Eastern Kenya in the context of adaptation to climate change. The objectives were to (i)describe farmer's perceptions on production of improved varieties of pigeon peas as an adaptation strategy to climate change, (ii) evaluate the impact of the adoption on household's net returns. Propensity score matching approach was used to assess the impact of the adoption. Methodology: The study used cross sectional data gathered through household survey to evaluate the impact of adoption on farming households' net farm returns in semi-arid South Eastern Kenya in the context of adaptation to climate change.. The study was conducted in semi-arid zones of Machakos County in South Eastern Kenya (SEK) namely Masinga, Mavoko and Mwala Wards. The areas were purposively selected for semi-arid semi-arid climatic conditions and dominant pigeon pea production.The study adopts the counterfactual approach and propensity score matching method to evaluate the impact of adopting improved pigeon peas on household net farm income. Data was analyzed using STATA 13.0 statistical package. Findings: The results showed that 33 percent of the sampled households had adopted production of improved pigeon peas and they perceived adoption of the technology as an adaptation strategy to climate change viewed through tolerance to drought, pest and diseases, increased crop yield and shortened crop growth period. Improved pigeon peas significantly increased farmers' net income, the adopter got a net farm income of KES 30,710 per acre per year that was KES 18, 631 more than non-adopting households. Unique contribution to theory, practice and policy: The study recommends that County Governments facilitate farmers to produce pigeon pea seeds through improved access to seed and linkage to reliable market for their farm produce to increase their farm income.